Effects of deflection angle on the mechanical properties of constant-resistance, energy-absorbing, and anti-scouring bolts - Tang, Zhi; Wu, Hao; Lv, Jinguo; Chang, Dezhi (Frontiers in Earth Science, 2023)
In practice, constant-resistance, energy-absorbing, and anti-scouring bolts inevitably deflect at an angle from the coal wall and other bearing surfaces, eventually giving way and losing their energy-absorbing function. The aim of this study was to determine the applicable range of deflection angles for constant-resistance, energy-absorbing, and anti-scouring bolts and to provide a reference design for bolt construction. The principle of application of bolts under various deflection angles was proposed, and the numerical simulation of use of constant-resistance, energy-absorbing, and anti-scouring bolts was carried out using ABAQUS finite element software. The effects of deflection angle, impact energy, and impact velocity on the deformation performance, load-bearing performance, and energy absorption performance of the bolts were investigated. The deformation process of the bolt based on deflection angle was found to change from axial stretching to “stretching and bending”. As the deflection angle increased, the load bearing capacity of the anti-punching device increased, and the bolt’s breaking force increased after decreasing, and then decreased again while absorption energy decreased non-linearly. The bolt yield distance decreased while the displacement of bolts remained essentially the same and the deflection distance of the anti-punching device decreased. The stroke efficiency of bolts decreased and, based on the design principles of constant-resistance, energy-absorbing, and anti-scouring bolts, it was determined that the bolt was still applicable within a deflection angle of 0–17°. The impact energy had a minor effect on the bolt indicators of yield force, breaking force, and energy absorption, and the bolt’s impact resistance time decreased non-linearly with increasing impact energy. Impact velocity had less effect on bolt yield force and breaking force. Both yielding time and anti-punching load capacity of the bolt decreased with increased impact velocity. As the impact velocity increased, yield distance, anti-punching deflection distance, and stroke efficiency all increased. The absorption energy increased linearly with increasing impact velocity. The results of this study provide a reference for similar anchor angle studies and a guide for the design of field construction.